2019
DOI: 10.1186/s12864-019-6280-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and characterization of F-box gene family in Gossypium hirsutum L

Abstract: BackgroundF-box proteins are substrate-recognition components of the Skp1-Rbx1-Cul1-F-box protein (SCF) ubiquitin ligases. By selectively targeting the key regulatory proteins or enzymes for ubiquitination and 26S proteasome mediated degradation, F-box proteins play diverse roles in plant growth/development and in the responses of plants to both environmental and endogenous signals. Studies of F-box proteins from the model plant Arabidopsis and from many additional plant species have demonstrated that they bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 86 publications
(134 reference statements)
3
17
2
Order By: Relevance
“…The ARID domain is related to sequence-specific DNA binding [ 52 ], the PHD domain specifically recognize methylated (modified) histone codes and may be important readers of histone codes [ 53 ], and the PLU-1 domain plays a critical role in gene regulation and chromatin stability [ 54 ]. In the JMJD6 subfamily, four JmjC genes ( GhJMJ3A/GhJMJ3D and GhJMJ18A/GhJMJ18D ) containing the F-box domain are consistent with previous study [ 55 ].…”
Section: Resultssupporting
confidence: 92%
“…The ARID domain is related to sequence-specific DNA binding [ 52 ], the PHD domain specifically recognize methylated (modified) histone codes and may be important readers of histone codes [ 53 ], and the PLU-1 domain plays a critical role in gene regulation and chromatin stability [ 54 ]. In the JMJD6 subfamily, four JmjC genes ( GhJMJ3A/GhJMJ3D and GhJMJ18A/GhJMJ18D ) containing the F-box domain are consistent with previous study [ 55 ].…”
Section: Resultssupporting
confidence: 92%
“…However, here, we found that 67% of the TaFBX genes do not have any additional known domains. This result is in accordance with the protein structure that has been observed in cotton and in wheat with, respectively, 54% and 76% of the FBX containing only the F-box domain [32,43]. A similar percentage was observed by Jain et al (2007) [41] in the rice FBX family.…”
Section: The Tafbx Family Structured Into Subfamilies Is Unequally Exsupporting
confidence: 91%
“…In contrast, only 14% and 30% of the FBX genes were identified without other known domains in Arabidopsis and chickpea, respectively [31,77]. The second most abundant subfamily was found to be the FBD subfamily in our study, such as in Hong et al (2020) [43], while this is the Kelch domain in cotton [32].…”
Section: The Tafbx Family Structured Into Subfamilies Is Unequally Excontrasting
confidence: 61%
See 1 more Smart Citation
“…The proposed systemic nomenclature will be helpful not only in introducing uniformity and communicating research findings effectively in the Arabidopsis FBP gene family but can also be applied to FBP gene families of other plant species whose genome sequencing have been completed and have well-defined chromosome maps. The genomic distribution of Arabidopsis FBPs depicts a positive relation between FBP number and chromosomal length as opposed to the study, which found out uneven FBPs distribution on cotton chromosomes ( Zhang et al, 2019 ; Figure 5 ). Targeting the genes involved in anther or pollen development can manipulate male fertility, which is of immense importance in crop breeding and increasing the crop yield ( Gómze et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 67%